Corporate Tax Management - Анна Юрьевна Исаева (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2010)
An increased focus on the tax function and its influence on business and financial performance efficiency is issue of present interest for modern Russian entities, tending to transparency, to enter stock market and act upon international financial standards. That is why the question about the possibility to adopt international experience in tax management implementation seems to be very interesting. The article states an analysis of tax management organization and adaptation in Russian and foreign companies. Based on the results of the search the author considers development prospects for tax management in Russia.